A prospective randomized pilot study comparing the short protocol with gonadotropin and gonadotropin-releasing hormone agonist to the combination of gonadotropin and gonadotropin-releasing hormone antagonist for ovulation stimulation in poor responder patients undergoing in vitro fertilization treatments - Donmez, Keziban Saylam; Delbaere, Anne (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: This study aimed to evaluate the effect of gonadotropin-releasing hormone antagonist for ovulation stimulation in poor responder patients undergoing in vitro fertilization treatments. Methods: Patients who had previously undergone two IVF cycles and had collected fewer than 5 oocytes in their last attempt, with a baseline FSH value below 15 IU/L, were selected to be included to the study. The patients were randomly included to one of the treatment groups. Before treatment, patients used oral contraceptive pills for 21 days. In Group A, recombinant gonadotropin was used with GnRH agonist in a short protocol. In Group B, recombinant gonadotropin was used with GnRH antagonist cetrorelix. Results: A total of 24 patients were included in the study. In Group A (11 patients), recombinant gonadotropin was used with GnRH agonist in a short protocol. In Group B (13 patients), recombinant gonadotropin was used with GnRH antagonist cetrorelix. The characteristics of the previous cycles for patients were also similar in both groups. Statistically, it was observed that the estradiol values in Group A were higher during ovulation induction. No significant difference was observed in the amount of gonadotropin used and stimulation durations in both groups. No significant difference was found in the number of oocytes collected. One pregnancy occurred in Group A, while 2 pregnancies occurred in Group B. A positive correlation was found between the baseline FSH value and the amount of gonadotropin used in Group B. Conclusions: There was no statistically significant difference in term of oocytes, embryo and pregnancy in the two groups. Larger-scale studies are needed to obtain definitive results.